Kinetics of arylation of 3-bromo-benzophenone with n-butylacrylate using NC palladacycle catalyst - Atla, Shashi B.; Rajurkar, Kalpendra B.; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2009)
The kinetics of arylation of n-butylacrylate (n-BA) with 3-bromo-benzophenone (BBP) using a monomeric palladacycle complex [Pd(ppy)(PPh(3))(OTs)](ppy=2-phenylpyridine) catalyst has been studied. The effect of concentration of the substrate, base (NaOAc), and catalyst was studied at three different temperatures (413-433 K). The rate was found to be first order with respect to catalyst, first order tending to zero order with respect to n-butylacrylate and NaOAc concentrations. The rate passed through a maximum with variation of BBP concentration. The observed results have been explained on the basis of formation of Pd species (PdX(2), PdX(3)(-), PdX(4)(2-), and Pd(2)X(6)(2-)) which are inactive for the Heck reaction. Various empirical rate equations were considered to fit the rate data and the best fitting model has been selected. The rates predicted by model were found to be in good agreement with the observed experimental data. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Arylation; Heck reaction; kinetics; Palladacycle